2022
DOI: 10.12659/msm.935080
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study to Evaluate the Effect of Dynamic Fracture Mobility on Cement Leakage in Percutaneous Vertebroplasty and Percutaneous Kyphoplasty in 286 Patients with Osteoporotic Vertebral Compression Fractures

Abstract: Background Cement leakage is the most common complication following percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs). Dynamic fracture mobility was determined by comparing preoperative standing lateral radiographs with intraoperative prone lateral radiographs. This retrospective study from a single center aimed to evaluate the effect of dynamic fracture mobility on cement leakage in PVP and PKP in 286 patients with OVCFs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Kyphoplasty also produces better immediate postoperative kyphosis correction and less progressive kyphotic degeneration than vertebroplasty and nonsurgical treatments [ 45 ]. The high incidence of cortical defects and instability of crushed vertebrae in TLBFs has been attributed to bone cement leakage [ 46 , 47 ]. Improvement in the components of conventional high-viscosity PMMA bone cement is necessary to prevent cement leakage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kyphoplasty also produces better immediate postoperative kyphosis correction and less progressive kyphotic degeneration than vertebroplasty and nonsurgical treatments [ 45 ]. The high incidence of cortical defects and instability of crushed vertebrae in TLBFs has been attributed to bone cement leakage [ 46 , 47 ]. Improvement in the components of conventional high-viscosity PMMA bone cement is necessary to prevent cement leakage [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While PKP was designed to reduce the incidence of cement leakage observed in PVP, [4] instances of cement leakage still occur in PKP. [28][29][30] Whether VBS could decrease the incidence of cement leakage is controversial. Werner et al [16] found no significant advantage of VBS over PKP with regard to cement leakage.…”
Section: Discussionmentioning
confidence: 99%
“…There is some controversy regarding the amount of bone cement injected; it has been suggested that the more adequate the dispersion of the bone cement, the better the pain relief; however, a higher amount of bone cement injected is more likely to trigger the risk of adjacent vertebral fracture and the probability of bone cement leakage. [19][20][21] Furthermore, bone cement leakage is a common postoperative complication of PKP, which may lead to nerve compression, and stimuli such as bone cement toxicity or allergy can cause symptoms such as decreased blood pressure and dyspnoea. 20,22 And, without compromising clinical outcomes, unilateral puncture requires only one set of puncture equipment, which can save patients' hospitalization costs.…”
Section: Discussionmentioning
confidence: 99%